АШЫТҚЫ ДАЙЫНДАУҒА АРНАЛҒАН СҮТҚЫШҚЫЛ БАКТЕРИЯЛАРДЫҢ КЕПТІРУ ТƏРТІПТЕРІН ЖАСАҚТАУ (Experimental biology, 2015)
Optimum modes and conditions of storage cultures microorganisms for the food-processing industry are investigated.
Keywords: microorganisms; food-processing